The Implementation of Dhuha Prayer Discipline Habituation in Shaping Character in Early Childhood at TK Ma’arif Alhidayah, Sekampung, East Lampung Regency - Ana Uswatun Hidayah; Anissatul Faqziaty; Nikmatur Rodiyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Implementation refers to everything that is carried out and applied according to a program designed to be executed fully in line with established regulations. The implementation of Dhuha prayer in the morning is carried out before the teaching and learning process begins, held every day without exception, performed collectively at the Babussalam Mosque located within the TK Ma’arif Al-Hidayah environment. The prayer consists of two rak’ahs performed at 07:30 AM Western Indonesian Time (WIB). The collective Dhuha prayer is initiated by classroom teachers to optimize both the quality and quantity of religious aspects while also serving as practical training for reciting in a clear, loud voice. Before performing the Dhuha prayer, students are required to recite sholawat and practice the adzan together. The habituation of Dhuha prayer discipline in early childhood requires the right stimuli. Establishing this discipline is crucial so that students can perform the Dhuha prayer properly. It is important to note that through repeated habituation of worship activities, children will become trained and find it easier to memorize prayer recitations. This research aims to describe the habituation of Dhuha prayer discipline among early childhood students in Group A and Group B at TK Ma’arif Al-Hidayah as a means of enhancing moral values. The study also explores the supporting and inhibiting factors in the implementation of this habituation. This is a qualitative study conducted at TK Ma’arif Al-Hidayah.